Alpha-mannosidosis in children: analysis of the observations and treatment options - A. N. Semyachkina (Rossijskij Vestnik Perinatologii i Pediatrii, 2020)
The article is devoted to a rare (orphan) disease from the group of lysosomal storage diseases — alpha-mannosidosis, associated with the accumulation of mannose-containing oligosaccharides in the tissues and cells of the body. The authors analyze the literature data and proposals of the International working group for the diagnosis of alpha-mannosidosis. The article presents the examination results of 15 patients with alpha-mannosidosis aged from 1 to 12 years. The diagnosis was based on the combination of phenotypic traits and extremely low activity of the lysosomal enzyme of alpha-mannosidase in peripheral blood lymphocytes. The molecular genetic verification of the diagnosis was performed in 14 probands. The authors found that all the patients under observation had a typical Hurler-like phenotype, lighter than patients with Hurler syndrome. The children were divided into 2 groups according to the severity of the disease: severe (1 child) and moderate (14 children) forms. The disease had a progressive course.The enzyme replacement therapy with velmanase alpha (recombinant human alpha-mannosidase), developed and registered in the European countries, is not used in Russia due to the absence of registration. Early diagnosis and early start of enzyme replacement therapy is the best way to limit the progression of the disease, and effective genetic counseling helps to prevent it.